Global strategic engagement : states and non-state actors in global governance - Marchetti, Raffaele (Lexington Books, 2016)
This book examines strategies to navigate today's global politics. It analyzes how the context is changing, the new actors playing within it, and the processes and mechanisms that they need to take into account in formulating their global strategies.